2014
DOI: 10.9734/air/2014/7142
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Conjugal Transfer of Vancomycin Resistance among Clinical Isolates of Staphylococcus aureus

Abstract: This work was carried out in collaboration between all authors. Authors GFMG and RMAEdesigned the study, wrote the protocol, and wrote the first draft of the manuscript. Author RMAE and HRA managed the literature searches, collection of samples, identification of VRSA, Antimicrobial susceptibility testing and the molecular studies. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Development of resistance to antibiotics in developing countries, like ours, seems to be mainly related to the unreasonable usage of antibiotics due to their easy availability without prescription at the drug stores, non-optimal use in hospitals, animal husbandry, fisheries and agriculture 20 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Development of resistance to antibiotics in developing countries, like ours, seems to be mainly related to the unreasonable usage of antibiotics due to their easy availability without prescription at the drug stores, non-optimal use in hospitals, animal husbandry, fisheries and agriculture 20 .…”
Section: Discussionmentioning
confidence: 81%
“…Also, it was stated by Dhanalakshmi, et al 24 that methicillin resistance represented 31.3% of SA isolates. Moreover, Abd El-Baky et al 20 found that methicillin resistance represented 25.4% of SA isolates in the study conducted for documentation of VRSA in the Minia University, Egypt.…”
Section: Discussionmentioning
confidence: 98%
“…According to many studies, the factors such as inadequately treated MRSA infection or colonization with VRE strains, and exposure to vancomycin, careless prescription of antibiotics, availability of antibiotics at the drugstores without prescription, lack of monitoring over nursing practices, extensive surgical procedures, prolonged hospitalization, serious underlying disease such as diabetes, malignancy, and renal failure are cited as the main risk factors for the emergence of VRSA (2,6,40).…”
Section: Discussionmentioning
confidence: 99%
“…The development of antimicrobial resistance in the Middle-East seems to be related to the selective pressure of vancomycin, the main antibiotic available to treat MRSA infections in the region, or due to the irrational application of antibiotics (6,12,14,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation